H- beam emittance analysis in a multicusp ion source. Issue 1 (1st April 2022) - George, A; Kalvas, T; Melanson, S; Dehnel, M; Broderick, N G R
Abstract: Emittance of the ion beam extracted from an ion source is dependent on the initial focusing action at the plasma sheath. The properties of the plasma sheath is further dependent on the local electric fields and charge densities around the sheath. Experiments are conducted for creating different sets of conditions around the plasma sheath in an H - multicusp filament ion source and the resulting emittance of the extracted H - ion beam is measured. Variation of beam emittance under different plasma densities, electrode voltages and gas flows are analysed.